(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The right to education is of paramount importance in the development of the individual. Article 41 of the Constitution of the Republic of Uzbekistan states that “Everyone has the right to education. Education for children is guaranteed by the state. School affairs are under state control.